Some transforming trends in science, technology and innovative services in the context of industrial revolution 4.0 in Vietnam - Tran Vu Tuan Phan; Nguyen Quoc Hung; Nguyen Xuan Hoa (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
In recent years, along with the continuous development of different types of technology, the development of innovation ecosystems, the models of science and technology service organizations have been changed greatly much. A number of legal documents guiding science and technology intermediaries, incubators, science and technology services, have been revised and updated, but there are still practical areas that have not been presented all the actual contents and trends of science, technology and innovation services. The science and technology services in this article are defined by the author based on the concept in the Law on Science and Technology (2013) and additional intermediary services of innovation support and innovation ecosystem development. Service types gradually shift towards integration between many services into a complete service package, linking many partners to provide services to customers, clearly defining customer needs. Transforming from simple case-based, contract-based service models to long-term subscription-based package services. Service revenue is changed from a one-shot contract to a subscription service (as service contract). Such a continuous shift will create many opportunities for organizations to deploy science, technology and innovation services, but also create many challenges. Code: 23111401